Staging avatarization :|potentiality, simultaneity, and in-betweenness in contemporary theatre - Aktan, Osman Can. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2022., 2022)
This thesis examines three American contemporary plays in the context of avatarization, which is characterized by three key features: potentiality, simultaneity, in-betweenness. Through the framework of these three pillars, it investigates the thematic and formal strategies followed in order to aptly represent the interwovenness of cyber and material spaces in the twenty-first century with a specific emphasis on how this intermingledness necessitates a cyberstage that can account for both of the spatialities involved. The three plays covered in the thesis are The Intelligent Design of Jenny Chow (2003) by Rolin Jones, Marjorie Prime (2016) by Jordan Harrison, and The (Curious Case of the) Watson Intelligence (2014) by Madeleine George. All of these plays, while exploring new territories through virtuality, hearken back to the prominent themes of modern American drama such as the reconstruction of nuclear family or the search for domestic bliss. Instead of producing theatre in the cyber realm or entirely immersing the artform into virtuality, these plays construct a symbiotic domain where the material and cyber elements cohabit the stage. In doing so, they address the virtual issues posed by avatarization while also not sacrificing the tactility of the traditional theatre stage. Therefore, this thesis concludes that, the formal and thematic theatrical innovations mimicking the interwovenness of different spatialities in the online age fashion a fresh medium that can both account for the domestic themes of modern drama and tackle the novel dilemmas presented by the concept of avatarization.
Keywords: Avatars (Virtual reality)